Influence of Communication on Consumer Purchasing Decision: A Study of Competing Sugar Brands - Omotola NEJO; Lanre AMODU; Oscar ODIBOH (Communications of International Proceedings, 2022)
This study examined the influence of Communication on consumers’ purchasing decision of two competing sugar brands in Nigeria. Anchored on the Elaboration Likelihood Model and Diffusion of Innovation theory, the study adopted the quantitative research design using the survey method. The random sampling technique applied provided a sample size of 250 respondents out of which 200 filled the questionnaire instrument correctly. Results were generated using the Scientific Package for the Social Sciences (SPSS). A key finding is the consumers’ preference for St. Louis sugar over Family sugar with no due reason. Further, it was revealed that taste and referrals from family and friends prompted consumers’ buying decision. The study concluded that there is a visible connection between Out-of-the-Box Communication and consumers’ decision-making concerning sugar brands in Nigeria. The study recommended that continuous research should be carried out periodically on other fast-moving consumer goods to provide useful data for positive consumer advocacy, food and drugs agencies’ monitoring, and retail product manufacturers and marketers, going forward.
Keywords: Brand; Strategy; Consumer Preference; Purchasing Decision; Communication